Transitional justice and victims' rights in Colombia - Romero Medina, Flor Alba (Ius Humani. Jornal do direito, 2025)
This article makes a report on the Peace Agreement signed between the Colombian government and the Revolutionary Armed Forces of Colombia, People's Army -FARC-EP-, after more than 5 decades of a degraded war, in which the civilian population has put the highest share of victims and suffering, and the decision to create, within the framework of said Agreements, the System of Truth, Justice, Reparation and Guarantees of Non-Repetition -SVJRNR-, in which the Special Jurisdiction for Peace -JEP- is the legal body of the system that acts from transitional justice, analizing its characteristics and benefits, with a restorative justice approach, in which the benefits of this type of justice are indicated, both for the victims and for the offenders, with the centrality on the victims of the armed conflict, victims who have been more widely recognized from said Agreements, where illegal armed actors, members of the public force and members of illegal armed groups are indicated as responsible, briefly indicating some restorative actions for the victims such as the reconstruction of the social fabric and healthy coexistence, support in the development of historical memory, work on infrastructure projects, and its significance in building a stable and lasting peace. Although retributive Justice has proven to be ineffective, restorative transitional Justice offers a different solution, on that connects perpetrators and victims; it is being implemented in the country, doubts and mistrust remain, both among victims and in society at large.